The Influence of Social Support and Subjective Well- Being on Student Engagement among Working Students at INABA University - Nurlela, Siti Agustin; Ekanesia, Pratidina (International Journal of Marketing & Human Resource Research, 2025)
This research seeks to explore how social support and subjective well-being contribute to student engagement among university students who balance academic responsibilities with part-time or full-time employment. Using a quantitative correlational design, the study involved 101 working students from the University Indonesia Membangun (INABA) as participants. Data were collected through standardized instruments : the Social Provisions Scale (SPS), the Satisfaction with Life Scale (SWLS), and the Student Engagement Scale (SES). Descriptive statistics revealed that more than half of the respondents experienced low levels of social support (52.5%) and subjective well-being (64.4%), while 51.5% reported low student engagement. Multiple linear regression analysis showed that both social support and subjective well-being significantly predicted student engagement, accounting for 40.4% of the variance. These findings underscore the significance of psychosocial resources in promoting academic engagement, particularly for students with dual roles. The results underscore the need for institutions to develop holistic strategies that not only enhance academic capacity but also nurture emotional well-being and supportive environments